NILAI KARAKTER TANGGUNG JAWAB DALAM SAJAK-SAJAK SUBAGIO SASTROWARDOYO - Sugeng Supriyono; Nugraheni Eko Wardani; Kundharu Saddhono (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2018)
Character’s Value Of Rerponsibilities from Subagio Sastrowardoyo Poems. The purpose of this study is to describe the value of responsibility character building of poems by Subagio Sastrowardoyo. This research includes descriptive qualitative research type with content analysis. Sources of data in this study book collection of Simfoni Dua by Subagio Sastrowardoyo. Techniques of collecting data using library techniques, refer method, and record. Data analysis technique uses interaction technique with stilistika approach. Based on the results of research that has been done, it is  found that the value of responsibility character building are implicit in the words, phrases, and sentences, ncluding spiritual responsibility to God, social responsibility to fellow human beings, and personal responsibility to yourself. The value of responsibility character building that is contained in the poems of Subagio Sastrowardoyo is relevant to literary learning which includes the competence of knowledge and skills of appreciating and writing poetry.